THE PERCEPTION OF AMBIGUOUS IMAGES AS A QUANTUM INFORMATION PROCESS (Istituto Lombardo - Accademia di Scienze e Lettere - Rendiconti di Scienze, 2014)
A simulation of the dynamic perception of the Necker cube in terms of a two level quantum system – e.g. a qubit realized by a Josephson junction or by an electron of spin ½ controlled by magnetic fields – indicates that the neuro-physiological transformation leading, through a symmetry reduction, to perceptual reversal is controlled by the principles of quantum mechanics. A value of the order of 0,32 mJ.s is estimated for the elementary neuro-physiological action simulating the Planck constant at a mesoscopic level. In this interdisciplinary study key concepts are utilized: symmetry, symmetry reduction, self-organization, superposition principle and ambiguity.